NATURALISTIC STUDY ON COMMUNICATION STRATEGY USED BY SIXTH SEMESTER STUDENTS IN MICROTEACHING CLASS OF ENGLISH DEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA - Rannisa Elly Fathin (Academy of Education Journal, 2017)
This research aims to describe communication strategy which is used by the sixth semester students in Microteaching class of English Department of Muhammadiyah University of Surakarta. This research is also reference to to minimize the problem which is occured during learning-teaching process. The data of this research is containing of communication strategy used by sith semester students in microteaching class of English Department of Muhammadiyah University of Surakarta. There are three sourcess data of this research, namely: event, informant, and document. The writer used descriptive qualitative to analyze the data. The process of classifying and counting the result of the data used Celce-Murcia taxonomy. The result of the data shows that there are 5 types with thirteen subtypes of communication strategies. Filler is the most dominant type of communication strategy with the percentage 43,90%, while the type that rarely used by the students is message abandonment, rephrsing, and appeal for help with the each percentage is 0,19%.